2005
DOI: 10.1002/polb.20708
|View full text |Cite
|
Sign up to set email alerts
|

Novel phosphate glass/polyamide 6 hybrids: Miscibility, crystallization kinetics, and mechanical properties

Abstract: The miscibility, crystallization kinetics, and mechanical properties of a novel low T g phosphate glass (Pglass)/polyamide 6 hybrid material were investigated. Here, we report the first evidence for miscibility of inorganic phosphate glass and organic polymer prepared by blending both components in the liquid phase using conventional polymer processing methods. From classical melting point depression measurements, we obtained a chi interaction parameter (v) of À0.067 for the Pglass/polyamide 6 hybrid, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…It was found that with the addition of Pglass into PET matrix, the values of T g , T oc and T cc of the PET/Pglass blends decreased at a given heating rate. The decreasing of T g values may arise from the plasticizing effect of Pglass which has been reported in the PA6/Pglass blend system [6]. In addition, the values of T m increased slightly with the addition of Pglass, indicating Pglass may induce the formation of thicker PET lamellae.…”
Section: The Morphologies Of the Pet/pglass Blendsmentioning
confidence: 92%
See 1 more Smart Citation
“…It was found that with the addition of Pglass into PET matrix, the values of T g , T oc and T cc of the PET/Pglass blends decreased at a given heating rate. The decreasing of T g values may arise from the plasticizing effect of Pglass which has been reported in the PA6/Pglass blend system [6]. In addition, the values of T m increased slightly with the addition of Pglass, indicating Pglass may induce the formation of thicker PET lamellae.…”
Section: The Morphologies Of the Pet/pglass Blendsmentioning
confidence: 92%
“…What is more, there is no intractable viscosity and dispersity problem which usually accompanys with composites processing with fillers such as talc, clay and glass fiber [3]. Several polymers such as PP [4], LDPE [5] and PA6 [6] have been successfully blent with Pglass for the production of novel hybrids.…”
Section: Introductionmentioning
confidence: 98%
“…This experimental observation is consistent with reported studies on Pglass/LDPE and Pglass/Polyamide 6 hybrid systems, where it was shown that the Pglass inhibited crystallite formation. 19,28,29 It is believed that the Pglass is acting similarly in the hybrid system of the present study and is a common feature of hybrid systems. The effect of melt-mixing speed on the percentage crystallinity is negligibly small.…”
Section: Crystalline Propertiesmentioning
confidence: 94%
“…Furthermore, because of the partial miscibility of the constituent phases, the local properties can vary in a nontrivial manner across the interfaces. 3,22,29 It is precisely a combination of all these factors that brings about the interesting and advantageous properties of the present hybrids. But it is also the same factors that make it so difficult to develop accurate theoretical equations for predicting the properties of the hybrids.…”
Section: Tensile Propertiesmentioning
confidence: 97%
“…The prominent peak above 50°C is typically attributed to the dynamic glass transition [56,57], although some authors dispute it [51]. We will come back to this point, in light of the results by the stochastic modulated DSC results.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 95%